Perilaku Penyimpangan Wartawan Tim Peliputan Berita (Studi Kasus Penyimpangan dalam Peliputan Berita di Stasiun Televisi Siaran) - Chendy Liana (Jurnal Dakwah dan Komunikasi, 2016)
This study focuses on the phenomenon about deviation behavior of news coverage team reporter. In doing their duties, reporters regulated and guided by the Code of Ethics in Journalism which insists journalist to be professional in carrying out their jobs and provide valuable news whichare objective, equilibrate, neutral, honest and based on facts. The purpose of this study isto determine the forms, methods, and factors which cause behavioral aberrations byjournalist ofnews coverageteam consistsby Reporter and Cameraman in the"X"TV station. The method used is a qualitative research with phenomenological approach. The subjects are eight journalists consisting of three senior and two junior reporters, two seniorand two junior cameramans. The results showed the forms of behavior irregularities committed by the journalist of news coverageteamin"X" TV stations is the rewardsacceptance by the term "envelope",falsification ofairedcopy, and the use of fictitious sources. The ways used by journalists of news coverage teamis obtaining informationsfromothers when doing the duties from their coordinators, and by approaching and contacting the informants directly. The causing factors of reporters’ deviated behavior